PENINGKATAN KOMPETENSI GURU SD MELALUI INOVASI PEMBELAJARAN PENDIDIKAN PANCASILA BERBASIS PROYEK DAN TEKNOLOGI AUGMENTED REALITY DI DESA KLAMBIR - Maulana Siregar, Waliyul; Jamaludin; Silalahi, Natalia; Luthfi Siregar, Hanif; Shaira Siregar, Khofifah (JS (JURNAL SEKOLAH), 2026)
Abstract: This community service program aims to enhance the competencies of elementary school teachers in developing project based Pancasila Education integrated with Augmented Reality (AR) technology. The activity was motivated by the limited use of technology and teachers’ low ability to implement the Project Based Learning model at SDN 101744, Desa Klambir. The implementation methods included socialization, training, AR-based learning implementation, mentoring, and evaluation. Teachers were trained to use the Assemblr Edu application to create AR media visualizing Pancasila values, particularly the theme of Indonesia’s cultural diversity. The results indicated a significant improvement in teachers’ digital literacy, with an average score of 4.83 (excellent category). Moreover, students’ learning outcomes increased from 55.5 to 86.5 after the AR media implementation. The program produced several outputs, including the AR Keragaman mobile application and website, project-based learning modules, guidebooks, and a draft of intellectual property rights (IPR). This activity demonstrates that integrating AR technology in project-based learning enhances teaching effectiveness, creativity, and students’ national character, serving as an innovative model for Pancasila Education in elementary schools. Keywords: Pancasila Education, Project Based Learning, Augmented Reality, Elementary School Teacher, Golden Generation